Adsorption and Thermal Desorption Behaviour of Asphalt-like Functionalities on Silica - Sangkwon Park; Myung-Chan Jo; Jun-Boum Park (Adsorption Science & Technology)
The adsorption and thermal desorption behaviours of seven model compounds containing asphalt-like functionalities were studied on silica. Adsorption isotherms of the model compounds were examined at 25°C and analyzed via the Langmuir isotherm. A series of temperature-programmed desorption (TPD) experiments was also conducted on the silica samples, the activation energy for desorption (E d ) being determined by conventional TPD analysis. The adsorption and thermal desorption behaviours were correlated in terms of the activation energy (E d tot ) for complete desorption. Dimethyl sulphoxide showed the strongest adsorption and the largest value for E d tot , implying that the high energy consumption necessary to desorb such functionalities plays a key role in the durability of asphalt–aggregate bonding.